A co‐designed framework to support and sustain patient and family engagement in health‐care decision making - Tamara L. McCarron; Thomas Noseworthy; Karen Moffat; Gloria Wilkinson; Sandra Zelinsky; Deborah White; Derek Hassay; Diane L. Lorenzetti; Nancy J. Marlett (Wiley, 2020)
Abstract Background Patient and family engagement in health care has emerged as a critical priority. Understanding engagement, from the perspective of the patient and family member, coupled with an awareness of how patient and family members are motivated to be involved, is an important component in increasing the effectiveness of patient engagement initiatives. The purpose of this research was to co‐design a patient and family engagement framework. Methods Workshops were held to provide additional context to the findings from a survey. Participants were recruited using a convenience sampling strategy. Workshop data collected were analysed using a modified constant comparative technique. The core research team participated in a workshop to review the findings from multiple inputs to inform the final framework and participated in a face validity exercise to determine that the components of the framework measured what they were intended to measure. Results The framework is organized into three phases of engagement: why I got involved; why I continue to be involved; and what I need to strengthen my involvement. The final framework describes seven motivations and 24 statements, arranged by the three phases of engagement. Conclusion The results of this research describe the motivations of patient and family members who are involved with health systems in various roles including as patient advisors. A deeper knowledge of patient and family motivations will not only create meaningful engagement opportunities but will also enable health organizations to gain from the voice and experience of these individuals, thereby enhancing the quality and sustainability of patient and family involvement.